Problems of Intercultural Communication and the Ways of Their Solution - Nabiev Obidjon Abdullo Ugli; Abdurasul Tukhtamishev (Indonesian Journal of Cultural and Community Development, 2020)
This research work will examine concepts that do not exist in another language that represent the national identity and culture of other peoples, develop methods and tools to translate them into language, understand their sociolinguistic roots in contemporary intercultural communication, and enhance learning.At present, the influx of people of different nationalities and cultures from different countries is increasing year by year, which underlines the importance of intercultural communication and its problems, as well as the ability of the interpreter to overcome these problems. In fact, language will always remain an integral part of society.